RANCANG BANGUN APLIKASI SURAT TUGAS DAN SURAT PERINTAH PERJALANAN DINAS PADA DINAS KESEHATAN KABUPATEN MAJALENGKA - Ummi, Fitri Syifaul; Susanti, Deffy (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid development of information technology has created a strong demand for more effective and efficient administrative systems, particularly within government institutions. One crucial element of administration in the public sector is the management of official documents such as Assignment Letters (Surat Perintah Tugas, SPT) and Official Travel Orders (Surat Perintah Perjalanan Dinas, SPPD). At the Health Office of Majalengka Regency, the preparation and management of these documents have traditionally been carried out manually, leading to inefficiencies, a higher risk of human error, and difficulties in archiving. This study aims to design and develop a web-based application for managing SPT and SPPD documents using the CodeIgniter framework. The system includes features such as automatic document generation with standardized templates, electronic approval workflows, centralized digital archiving, and document tracking functionalities. The Rational Unified Process (RUP) methodology was applied in the development stages, covering inception, elaboration, construction, and transition. The results indicate that the application successfully automates the creation and management of SPT and SPPD documents, significantly improving efficiency, accuracy, and accessibility. Digital archiving ensures better security and faster retrieval of documents, while the user-friendly interface allows employees to operate the system with minimal training. The implementation of this system supports the digital transformation initiatives of local government agencies and contributes to improving the quality of public services in the health sector.